The Oromo Language Use in Wellega Dioceses: Opportunities and Challenges: Yohannes Adigeh (PhD) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2013)
It is possible to find examples of “‘sacred’ language for special religious activities and of ‘secret’ language not allowed and often incomprehensible to non-members of a particular group of people who adhere to special cults of worship or belong to secret societies in Africa.” Some countries, which have a national religion, have specific languages of religion. For example, the Vatican Catholic Church uses Classical Latin for different functions of spiritual ministry. The Arabic language is the main symbol of cultural and religious unity among peoples leaving in Arabian countries.2 Consequently, language and religion are inseparable in the Qur’an, the sacred scripture of Islam. Sanskrit, the classical sacred and literary language of the Hindus of India is used only for religious purposes.